2002
DOI: 10.1523/jneurosci.22-19-08647.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating Striatal and Hippocampal Function Developmentally with a Stimulus–Response Compatibility Task

Abstract: The current study examined the development of cognitive and neural systems involved in overriding a learned action in favor of a new one using a stimulus-response compatibility task and functional magnetic resonance imaging. Eight right-handed adults (mean age, 22-30 years), and eight children (7-11 years) were scanned while they performed a task. Both children and adults were less accurate for incompatible stimulus-response mappings than compatible ones; the children's performance was significantly worse. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 58 publications
12
103
0
2
Order By: Relevance
“…Both tasks included items that were phonologically similar, but orthographically dissimilar (e.g., hope-soap), so participants had to ignore irrelevant orthography to make a rhyming judgment and irrelevant phonology to make a spelling judgment. Previous studies show that children's ability to enhance the processing of task-relevant information (Richards, 2003;van der Stelt et al, 1998) and suppress interference from information that is irrelevant to the task is weaker compared to adults (Bunge et al, 2002;Casey et al, 2001Casey et al, , 2002Tipper et al, 1989;Williams et al, 1999). We suggest that weaker control of the IFG over posterior regions underlies the children's relative difficulty in performing the tasks in the current study.…”
Section: Discussionmentioning
confidence: 44%
“…Both tasks included items that were phonologically similar, but orthographically dissimilar (e.g., hope-soap), so participants had to ignore irrelevant orthography to make a rhyming judgment and irrelevant phonology to make a spelling judgment. Previous studies show that children's ability to enhance the processing of task-relevant information (Richards, 2003;van der Stelt et al, 1998) and suppress interference from information that is irrelevant to the task is weaker compared to adults (Bunge et al, 2002;Casey et al, 2001Casey et al, , 2002Tipper et al, 1989;Williams et al, 1999). We suggest that weaker control of the IFG over posterior regions underlies the children's relative difficulty in performing the tasks in the current study.…”
Section: Discussionmentioning
confidence: 44%
“…Using source localization methods, Jonkman and colleagues found that the neural activity underlying response inhibition in adults was adequately explained by frontal sources, but in children, contributions from additional posterior sources were required. Supporting evidence also comes from studies utilizing brain imaging techniques that have shown that as children develop, the neural networks controlling inhibitory processes shift from a more posterior, distributed pattern to a more frontal, localized one (Bunge et al, 2002; Casey, Thomas, Davidson, Kunz, & Franzen, 2002; Durston et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…This example of initial diffuse cortical activity early in learning, followed by an increase in focal activity, parallels results from developmental fMRI studies. These studies show diffuse activity in children relative to adolescents and adults, with adolescents showing the greatest focal activity during performance of behavioral tasks, even when performance across groups is equated [24][25][26][27][28][29].…”
Section: Neural Changes During Learningmentioning
confidence: 90%